SHARP PIN INHALATION IN TRACHEO-BRONCHIAL TREE IN WOMEN WEARING HIJAB - Benyan, Abdul Khalik Z; Al-Hassani, Fouzi AA; Kareem, Dhia R (Journal of Postgraduate Medical Institute, 2012)
Objective: To investigate the presence of sharp pin inhalation in tracheo-bronchial tree in women wearinga hijab. Methodology: This was a descriptive study that was conducted in the thoracic surgical department in alsaderteaching hospital, Basra from February 2010 to March 2011. Detailed history was taken from all thepatients. Clinical examination, chest radiography and rigid bronchoscopy under general anesthesia weredone to all the patients included in the study. In those, where rigid bronchoscopy failed to remove the pin,thoracotomy was done. Results: The mean age of the sample was 19.5 years. All females presented with cough while two of themhad hemoptysis (5.5%) and five had unilateral wheeze on chest auscultation (13.8%). The majority (n=28,77.8%) of pins were located in the left main bronchus. The rest were either in the right main bronchus(n=5, 13.8%) or in trachea (n=3, 8.4%). Pins from 32 (88.9%) patients were removed by Negus rigidbronchoscopy. In only 4 (11.1%) patients, thoracotomy was done to remove the foreign body. Conclusion: Sharp pin inhalation is a serious hazard and can have lethal outcome. It commonly occurswhen women hold the pins in their teeth while wearing the hijab and talking to others at the same time.